Distribution Characteristics of Pea Gravel Behind Segment in Shield Tunnel Boring Machine Tunnels - Shengzhi WU; Honghai ZHAO; Hongqiang XIE; Yucang DONG; Lin FANG; Mingnian WANG; Yue LIU (工程科学与技术, 2024)
Pea gravel plays a crucial role in segment stability as the connecting layer between the segment and the surrounding rock in TBM tunnels. Due to the influence of construction technology and geological conditions, the phenomena of dense filling and uneven distribution of pea gravel often occur, leading to various disasters such as dislocation, cracking, and water leakage. The distribution characteristics of pea gravel behind the segment ring form the basis for analyzing segment stress. Within the context of the Qingdao metro TBM tunnel project, geological radar is employed to examine the distribution characteristics of pea gravel behind the segment wall. Subsequently, a numerical simulation of single-ring pea gravel filling is conducted. This study analyzes the migration process of pea gravel behind the segment wall in both straight and curved sections of the tunnel and discusses the impact of geological conditions, filling pressure, collapses, and other factors on the quality of the filling. The results indicated that during TBM tunnel construction, the arch crown, tunnel bottom, and lower part of the outer side of the line’s turning section are the areas most prone to pea gravel empty tunnels. Moreover, the pea gravel empty of the arch crown and tunnel bottom exceeds 1 m, while those at the lower part of the outer side of the turning section are smaller and less dense. Poorer geological conditions increase the probability and scale of voids in the pea gravel behind the segment, with strongly weathered strata showing the most significant effects. Collapses impact pea gravel reclamation by obstructing migration paths and increasing energy demands, although their impact is limited to the collapse site. Enhancing the hydraulic fill pressure of the pea gravel can improve the fill quality at the vault and tunnel bottom; the improvement is more pronounced under better geological conditions, though it does not significantly enhance the filling quality in strongly weathered strata. Based on the causes of formation, the pea gravel cavities behind the segment ring are categorized into three types: collision energy dissipation, collapse block, and smaller clearance in the turning section. Additionally, the study presents the frequent parts, characteristics, and construction recommendations related to these activities.